MODERN TREATMENT METHODS FOR HEPATORENAL SYNDROME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
A dangerous side effect of severe liver disease that results in kidney failure is hepatorenal syndrome (HRS). Assessing the clinical, pathogenetic, and genetic variables that affect the onset and prognosis of hepatorenal syndrome in the Khorezm region of Uzbekistan is the aim of this study. The role of genetic predisposition, pathogenetic processes, and clinical markers was examined in a retrospective study of 50 patients with HRS diagnosed at regional hospitals. The results show a substantial correlation between certain genetic markers, pathogenetic factors, and clinical outcomes, which may improve the prognosis and treatment of hepatorenal syndrome patients in the area.